Implant Removal Versus Implant Retention Following Posterior Surgical Stabilization of Thoracolumbar Burst Fractures: A Systematic Review and Meta-Analysis. Issue 4 (May 2022) - Kweh, Barry Ting Sheen; Tan, Terence; Lee, Hui Qing; Hunn, Martin; Liew, Susan; Tee, Jin Wee
Study Design: Systematic review and meta-analysis. Objectives: To compare biomechanical and functional outcomes between implant removal and implant retention following posterior surgical fixation of thoracolumbar burst fractures. Methods: A search of the MEDLINE, EMBASE, Google Scholar and Cochrane Databases was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Results: Of the 751 articles initially retrieved, 13 published articles pooling 673 patients were included. Meta-analysis revealed there was a statistically significant improvement in sagittal Cobb Angle by 16.48 degrees (9.13-23.83, p < 0.01) after surgical stabilization of thoracolumbar burst fractures. This correction decremented to 9.68 degrees (2.02-17.35, p < 0.01) but remained significant at the time of implant removal approximately 12 months later. At final follow-up, the implant removal group demonstrated a 10.13 degree loss (3.00-23.26, p = 0.13) of reduction, while the implant retention group experienced a 10.17 degree loss (1.79-22.12, p = 0.10). There was no statistically significant difference in correction loss between implant retention and removal cohorts (p = 0.97). Pooled VAS scores improved by a mean of 3.32 points (0.18 to 6.45, p = 0.04) in the combined removal group, but by only 2.50 points (-1.81 to 6.81, p = 0.26) in the retention group. Oswestry Disability Index scores also improved after implant removal by 7.80 points (2.95-12.64, p < 0.01) at 1 year and 11.10 points (5.24-16.96, p < 0.01) at final follow-up. Conclusions: In younger patients with thoracolumbar burst fractures who undergo posterior surgical stabilization, planned implant removal results in superior functional outcomes without significant difference in kyphotic angle correction loss compared to implant retention.